Next-Generation Sequencing Analysis of 3 Uterine Adenosarcomas with Heterogeneously Differentiated Genomic Mutations - Yao Li; Xue Meng; Yuqing Luo; Xiang Huang; Shuai Luo; Jinjing Wang (International Journal of Analytical Chemistry)
Uterine adenosarcoma (UA) is an uncommon mixed tumor containing a benign to at most mildly atypical epithelial component and a sarcoma-like stroma, usually a low-grade, stromal component, with rare heterogeneous elements. Currently, tumor etiology is largely unknown. To better understand the gene mutations in UA, next-generation sequencing (NGS) technology analysis was performed. This study showed that two low-grade UAs with heterologous components had ATRX gene frameshift mutation, and one patient had a MED12 missense mutation. Copy number amplification genes were mainly observed on chromosome 12q13–15. In this study, PIK3/AKT/PTEN pathway mutations were found to be common in adenosarcoma. In addition, a rare BCORL1-PRR14L fusion mutation was also identified. These findings provide a basis for future research into these molecular changes in tumorigenesis and targeted therapy.